Analysis of Species in Meat Products in Bandung City using Multiplex PCR - Yelliantty Yelliantty; Ira Endah Rohima (Pasundan Food Technology Journal (PFTJ), 2018)
Cases concerning the substitution of meat raw material also occur in Indonesia and are quite common. Therefore, careful monitoring and control that needs to be done on the meat products. Screening or sampling products on the market should be conducted periodically to ensure the safety of consumers and society in general. Such screening should be done accurately. This study aimed to analyze the composition of meat in processed products in traditional markets in Bandung using PCR method. This study was using four specific primers to detect four different species. Screening is done on samples of meatballs from several markets. The results showed the presence of several samples that contain meat of some species. based it can be concluded that the substitution of raw materials processed meat products also occurs in the traditional market in the city of Bandung, and the PCR method referred to can be used as the basis for the development of detection methods of food security in Indonesia.